In-line measurement of multiphase flow viscosity - Taisiia Ushkova; Alexandra Kopteva; Vadim Shpenst; Tole Sutikno; Mohd Hatta Jopri (Bulletin of Electrical Engineering and Informatics, 2022)
The transportation modes depend entirely on the viscosity of the oil. To date, none of the viscometric methods are able to provide measurements to meet all the requirements of oil flow, features of main oil pipelines, and trends in the oil industry, such as decarbonization and digitalization. The method of inline viscosity measurement of multiphase flow through a metal pipeline can be based on direct gamma ray measurement. It is stipulated by the ability of gamma-radiation to penetrate through the pipeline material without destroying it, as well as by the ability to work with flows containing free gas and the high capability to be introduced into automatic control systems. The authors consider the physical forces acting on the gas inclusions in the oil flow. They determine the physical dependence between the parameters determined by the radioisotope method and the viscosity of oil in the three-phase flow. These studies show good agreement with the work of other scientists. The prospect of further research will be to clarify the mathematical model of gas-oil flow, to increase the accuracy by reducing the number of assumptions made.